2021
DOI: 10.3389/fmicb.2021.737042
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Bacterial Community of Allopatric Przewalski’s Gazelles and Their Sympatric Relatives

Abstract: Mammal gastrointestinal tracts harbor diverse bacterial communities that play important roles in digestion, development, behavior, and immune function. Although, there is an increasing understanding of the factors that affect microbial community composition in laboratory populations, the impact of environment and host community composition on microbiomes in wild populations is less understood. Given that the composition of bacterial communities can be shaped by ecological factors, particularly exposure to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
3
7
0
Order By: Relevance
“…Thus, the differences in bacterial community composition between wild and captive animals may result from the differences in diet. A similar result was also found by Liu et al (2021) [ 46 ] that the bacterial beta diversity of the wild population was distinct from that of the captive population.…”
Section: Resultssupporting
confidence: 88%
“…Thus, the differences in bacterial community composition between wild and captive animals may result from the differences in diet. A similar result was also found by Liu et al (2021) [ 46 ] that the bacterial beta diversity of the wild population was distinct from that of the captive population.…”
Section: Resultssupporting
confidence: 88%
“…The blood physiological atlas provides a reliable information about the health of animals, and also reflects their response to internal and external environment ( 24 , 25 ). However, as the season changes, intestinal microbes and blood physiology also change ( 26 , 27 ). However, with seasonal changes, the relationship between intestinal microbes and blood physiological indicators are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown decreasing community similarity with increasing differences between habitats and species (Liu et al, 2021;Barrionuevo et al, 2022;Yang et al, 2022), and that animal sex is also a predominant factor affecting the gut microbiota (Zhang et al, 2022). Although the direct analysis method did not reflect the differences in gut microbiota by sex (Supplementary Figure 2B), significant differences were revealed by using a supervised analysis method (PLS-DA) (Figure 2).…”
Section: Discussionmentioning
confidence: 99%